1995
DOI: 10.1515/bchm3.1995.376.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins D, B and L in Breast Carcinoma and in Transformed Human Breast Epithelial Cells (HBEC)

Abstract: An increased expression of lysosomal enzymes, cathepsin (Cat) D, Cat B and Cat L, was observed in various human tumours and after in vitro cell transformation. To establish possible co-ordination in their expression, all three cathepsins were determined in human breast tumours and in transformed human breast epithelial cells (HBEC). In breast carcinoma (n = 120) all three cathepsins, determined immunochemically and by enzymatic activity, were increased compared to normal breast tissues. The activities, correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Enzyme activity in the media could be activated by pepsin, resulting in a several fold increase in Cat B activity ( Table 1). The highest activation was observed in the medium of the D3-1Tras cell line, in agreement with our immunochemical data showing that Cat B was secreted mostly as a 46 kDa precursor [25,26]. Immunocytochemical analysis showed heterogeneity in intracellular Cat B staining: only 5-20% of cells in the control and carcinogen-treated lines seemed to express Cat B (Fig.…”
Section: Biochemical Changes Induced In the Carcinogen And C-ha-ras Osupporting
confidence: 90%
See 1 more Smart Citation
“…Enzyme activity in the media could be activated by pepsin, resulting in a several fold increase in Cat B activity ( Table 1). The highest activation was observed in the medium of the D3-1Tras cell line, in agreement with our immunochemical data showing that Cat B was secreted mostly as a 46 kDa precursor [25,26]. Immunocytochemical analysis showed heterogeneity in intracellular Cat B staining: only 5-20% of cells in the control and carcinogen-treated lines seemed to express Cat B (Fig.…”
Section: Biochemical Changes Induced In the Carcinogen And C-ha-ras Osupporting
confidence: 90%
“…In general, secretion of the precursor form(s) results mostly from an inefficient interaction between the lysosomal enzyme precursors and the mannose-6-phosphate or other receptors in the trans Golgi network [28]. This may have occurred in both c-Ha-ras transformed cell lines, where markedly lowered intracellular concentrations of the precursors were found [26]. The synthesis and the secretion of a lysosomal enzyme are under different control mechanisms and may not be linked.…”
Section: Discussionmentioning
confidence: 99%
“…49) An increased expression of cathepsin-D in malignant breast tissue when compared to normal breast tissue observed in our investigation is in line with previous reports. 50) Reversion of their levels in drug treated animals may be due to the stabilizing property of the drug on lysosomal membrane which could have been imparted by the flavonoids, as it is well established that flavonoids have inhibiting property on lysosomal membranes. The drug may modify the lysosomal membrane in such a way that it is capable of fusing with the plasma membrane and thereby preventing the discharge of acid hydrolases or by inhibiting the release of lysosomal enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported increased expression, activity and/or altered cellular localization of individual cathepsins, in particular cysteine cathepsins, in human cancers. Increased levels of cathepsins B and H have been found in tumors of breast cancer patients, and cathepsin B tumor expression levels correlated positively with a poor prognosis (5)(6)(7)(8)(9)(10)(11). Cathepsin X has been studied far less in cancer, with only 2 studies reporting on its expression in tumors.…”
Section: Introductionmentioning
confidence: 99%